2012
DOI: 10.1128/jb.00966-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Broad-Host-Range Strain Sinorhizobium fredii USDA257

Abstract: Here we announce the complete genome sequence of the symbiotic and nitrogen-fixing bacterium Sinorhizobium fredii USDA257. The genome shares a high degree of sequence similarity with the closely related broad-host-range strains S. fredii NGR234 and HH103. Most strikingly, the USDA257 genome encodes a wealth of secretory systems. Sinorhizobium fredii USDA257 is a Gram-negative soil bacterium that fixes nitrogen in symbiosis with legume plants. It was originally isolated from wild soybean cultivars (1) and has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…syrM, nodD3, and syrA appear to be universal in the Sinorhizobium genus based on published genome sequences (95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Among S. meliloti and S. medicae strains, the orthologous proteins are nearly identical, and the gene arrangement is syntenic to S. meliloti Rm1021 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…syrM, nodD3, and syrA appear to be universal in the Sinorhizobium genus based on published genome sequences (95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Among S. meliloti and S. medicae strains, the orthologous proteins are nearly identical, and the gene arrangement is syntenic to S. meliloti Rm1021 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequences were downloaded from GenBank, and the corresponding accession numbers are as follows: AL591688.1 (S. meliloti 1021 chromosome) (41), AL591985.1 (S. meliloti 1021/pSymB) (15), CP001832.1 (S. meliloti SM11/pSmeSM11d) (42), CP002782.1 and CP002742.1 (S. meliloti AK83 chromosome 2 and S. meliloti BL225C/ pSINMEB02) (43), CP000738.1 and CP000739.1 (Sinorhizobium medicae WSM419 chromosome and pSMED01) (44), CP001389.1 and CP000874.1 (Sinorhizobium fredii NGR234 chromosome and pNGR234b) (45), NC_016812.1 (S. fredii HH103 chromosome) (46), and CP003563.1 (S. fredii USDA 257) (47).…”
Section: Methodsmentioning
confidence: 99%
“…4), the tree showed that both the engA and tRNA arg genes were located on the main chromosome, except in the case of all sequenced S. meliloti strains (15 strains) and S. medicae WSM419 (16,43,44,54,55). Furthermore, both the engA and tRNA arg genes were located on the chromosome for Sinorhizobium fredii strains NGR234, USDA257, and HH103 (45)(46)(47) and nine recently sequenced Sinorhizobium strains (seven S. fredii strains, one Sinorhizobium sojae strain, and one Sinorhizobium sp. strain [56]).…”
Section: Figmentioning
confidence: 98%
“…Sinorhizobium fredii strain GR64 was isolated in Granada, Spain (4). Usually, S. fredii strains are able to nodulate soybean (Glycine soja) (7,8,10); however, S. fredii GR64 was isolated from bean nodules and is unable to nodulate soybean (2). One of the plasmids (pSfr64a) of GR64 has been sequenced.…”
mentioning
confidence: 99%
“…Two libraries were sequenced with Illumina: one of 2-kbp mate pairs (8,163,266 reads, 400 Mbp) and the other one of 350-bp paired ends (8,555,556 reads, 760 Mbp). The Illumina reads were assembled by the SOAPdenovo method (6), resulting in 188 contigs.…”
mentioning
confidence: 99%